External Memory Aid Preferences of Individuals with Mild Memory Impairments - Lanzi, Alyssa; Wallace, Sarah E.; Bourgeois, Michelle S. (Seminars in Speech and Language, 2018)
Individuals with mild memory impairments often rely on external memory aids (EMAs) to compensate for impaired cognitive abilities and to support independent completion of activities of daily living. These strategies are evidence based; however, professionals have limited knowledge regarding individual preferences and guidance on how to incorporate a person-centered approach into the EMA development phase. The purpose of the current study was to qualitatively investigate individuals' preferences and experiences as they relate to EMAs. Data analysis included (1) evaluation of a posttreatment questionnaire to explore individual strategy preferences following intervention and (2) evaluation of group intervention videos using thematic coding to investigate individuals' experiences with strategies during intervention. Results suggest that older adults with mild memory impairments have unique preferences and experiences, despite limited variability in demographic characteristics. Some themes that emerged included memory ability awareness and attitudes toward technology. Within a person-centered approach, skilled professionals must consider individuals' unique needs, preferences, and experiences when developing strategies throughout the continuum of care to promote sustained EMA use within everyday settings.
Keywords: person-centered care; external memory aids; preferences; neurocognitive; disorder; older adults